Space time of crowd evacuation from a room with two exits. (2016) - Au, ChiKit
This article discusses how the spatial structure is linked to the social behaviour by considering the crowd evacuation from a room with two exits. The individuals are represented by a group of particles. By considering the space time of the room, a room is partitioned into regions associated with the exits. The particles select their exits to leave the room based on their positions in these partitions and follow the path of least time. The change of environment such as the crowd size around the selected exit will be reflected on the partition and the particle may change its mind accordingly. Before a particle reaches an exit, it joins the crowd accumulated at that exit. This shows how the crowd accumulated around the exit influence the particle decision during the evacuation and their decisions affect the congestions around the exits.